Pedicle Screw Configuration for Thoracolumbar Burst Fracture Treatment: Short versus Long Posterior Fixation Constructs with and without Anterior Column Augmentation - Peters, Todd (Korean Society of Spine Surgery, 2014)
STUDY DESIGN: An in-vitro study. PURPOSE: The current study is aimed at investigating the differences in stability between short posterior fixation (SPF), hybrid posterior fixation (HPF), and long posterior fixation (LPF) with and without anterior column augmentation using calcium phosphate bone cement (CaP) for treating burst fractures (BFs). OVERVIEW OF LITERATURE: The ideal treatment for thoracolumbar BF is controversial regarding the use of short or LPF constructs. METHODS: Seven human thoracolumbar spines (T9-L4) were tested on a six degree of freedom spine simulator in three physiologic planes, flexion-extension (FE), lateral bending (LB), and axial rotation (AR). Tested surgical constructs included the following: intact, injury (BF), SPF (T12-L2), HPF (T11-L2), LPF (T11-L3), SPF+CaP, HPF+CaP, LPF+CaP, and CaP alone (CaP). Range of motion (ROM) was recorded at T12-L2 in FE, LB, and AR. RESULTS: The reduction in mean ROM trended as follows: LPF>HPF>SPF. Only LPF constructs and HPF with anterior column augmentation significantly reduced mean ROM in FE and LB compared to the intact state. All instrumented constructs (SPF, HPF, and LPF) significantly reduced ROM in FE and LB compared to the injured condition. Furthermore, the instrumented constructs did not provide significant rotational stability. Injecting CaP provided minimal additional stability. CONCLUSIONS: For the injury created, LPF and HPF provided better stability than SPF with and without anterior column augmentation. Therefore, highly unstable fractures may require extended, long or hybrid fusion constructs for optimum stability.